Nutritional Status and Toddler Development: Cross-Sectional Study at Mawar Health Post, Tegal Harum Village - Natha, Florensia Sutji Putri; Puspa Negara, Anak Agung Gede Angga; Vittala, Govinda; Pramita, Indah (Majalah Ilmiah Fisioterapi Indonesia; Vol 12 No 3 (2024): Majalah Ilmiah Fisioterapi IndonesiaDO - 10.24843/mifi.2024.v12.i03.p02, 2024)
Introduction : Development is an integral part of the human life cycle, and the under-five years old (toddlers) period is crucial in this process. A child's nutritional status is one aspect that influences development across various domains. However, stunted development and malnutrition persist, particularly in Indonesia. Bali province, especially Denpasar City, exhibits a high level of good nutritional conditions. Nevertheless, some children still face problems, including excessive, inadequate, or poor nutrition. This study aims to determine the relationship between nutritional status and toddler development at the Mawar Integrated Health Post in Tegal Harum Village. Methods : The research employed an analytical observational approach with a cross-sectional design. Purposive sampling was used to select 58 children under five as subjects. Data collection involved measuring nutritional status using Weight-for-Age (WAZ) and toddler development using the Pre-Screening Development Questionnaire (PSDQ). Results : A chi-square test was conducted to analyze the relationship between nutritional status and toddler development. The results showed a significant relationship with a p-value of 0.000 < 0.05. Conclusion : Based on the findings, it can be concluded that there is a significant relationship between nutritional status and toddler development at the Mawar Integrated Health Post in Tegal Harum Village.   Keywords : nutritional status, development, toddlers